Ocorrência de Meloidogyne enterolobii Yang & Eisenback, no município de Uberlândia, Minas Gerais, Brasil - Almeida, Eduardo Jose [UNESP]; Santos, Jaime Maia [UNESP] (Universidade Federal de Uberlândia (UFU), 2011)
Meloidogyne enterolobii Yang & Eisenback (Sin.: M. mayaguensis Rammah & Hirschmann), poliphagous plant parasitic nematode, has been reported causing hard damage in several plant species in Brazil. This communication represents the first occurrence of this nematode in the municipality of Uberlandia, Minas Gerais State, Brazil.

Meloidogyne mayaguensis Rammah & Hirschmann, fitonematóide polífago, vem sendo registrado causando severos danos em diversas espécies botânicas pelo Brasil. Este comunicado registra pela primeira vez a ocorrência desse nematóide no Sul do Estado de Minas Gerais, no município de Uberlândia.
Occurrence of Meloidogyne enterolobii in the municipality of Uberlândia, state of Minas Gerais, Brazil
Keywords: Nematology; Rot knot nematode; Plant pathology